Master Narratives of the Middle Ages in Bulgaria - Daskalov, Rumen, 1958- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2021)
This volume offers a history of historiography, as Roumen Daskalov presents a critical analysis of Bulgarian historiographical views of the Middle Ages to reveal their embeddedness in their historical context and their adaptation to the contemporary circumstances. The study traces the establishment of a master narrative of the Bulgarian Middle Ages and its evolution over time to the present day, including the attempt at a Marxist counter-narrative. Daskalov uses categories of master national narratives, which typically are stories of origins and migrations, state foundations and rises ("golden ages"), and decline and fall, yet they also assert the continuity of the "people", present certain historical personalities (good or evil, "great" or "weak"), and describe certain actions or passivity to others' actions.